PENGARUH RASIO PROFITABILITAS, RASIO AKTIVITAS, INVESTMENT OPPORTUNITY SET, DAN KEBIJAKAN DIVIDEN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2017-2021 - Azhari, Anggun; HP, Agustin; Sari, Nurshadrina Kartika (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2024)
This study aims to analyze the influence of the variable profitability ratios, activity ratios, Investment Opportunity Set (IOS) and dividend policy on profit growth with sector manufacturing companies consumer non cyclicals as an object of research. This research was conducted over a period of five years, from 2017 to 2021 with a total sample of 14 companies. Sampling in this study using the technique purposive sampling and data were analyzed using multiple linear regression analysis. The results showed that partially the profitability ratio, activity ratio, Investment Opportunity Set (IOS) has no effect on profit growth while the dividend policy variable has an effect on profit growth. Simultaneously variable profitability ratios, activity ratios, Investment Opportunity Set (IOS), and dividend policy has an influence on profit growth.